Strengthening Legal Certainty of Marriage Contract (Ijab Kabul ) via Telecommunications in the Digital Era and Its Alignment with Sustainable Development Goal : Case of Indonesia - Muhyidin; Setyawan, Budi; mohiddin, Mas nooraini hj; Setyowati, Ro’fah; Musyafah, Aisyah Ayu; Sarono, Agus; Islamiyati (Pandecta Research Law Journal, 2025)
This research investigates the legal implications and challenges of adapting ijab kabul (Islamic marriage contract) to the digital era in Indonesia. The rise of telecommunications technologies—especially video calls—has enabled remote marriages during the COVID-19 pandemic and in geographically separated contexts. While digital ijab kabul offers efficiency and broader access, questions persist regarding its legal validity, potential for fraud, and regulatory ambiguity. Currently, Indonesia’s Marriage Law No. 1 of 1974 requires physical presence for marriage to be legally valid. However, the Indonesian Ulema Council (MUI) has issued a fatwa allowing digital ijab kabul under specific conditions: real-time audiovisual communication, verified identities, and a shared session (ittihad al-majlis). These criteria demonstrate partial acceptance of digital presence under Islamic law, yet lack binding legal force. Using a normative juridical approach, this study analyzes statutory law, Islamic legal doctrines, and international comparisons with countries like Malaysia, Saudi Arabia, and the UAE. These nations have developed legal frameworks for digital marriage by enforcing identity verification (biometrics, e-signatures) and procedural integrity. The study proposes that Indonesia revise Article 26 of the Compilation of Islamic Law (KHI) to explicitly recognize digital ijab kabul, harmonizing it with Law No. 11/2008 on Electronic Information and Transactions (ITE Law). By formally acknowledging digital presence within ittihad al-majlis, Indonesia can ensure greater legal certainty and protect vulnerable parties. This legal reform supports Sustainable Development Goal (SDG) 16 by promoting access to justice, enhancing legal institutions, and fostering trust in digital innovations within religious and civil legal systems.